Hemographic indices are associated with mortality in acute heart failure - Huang, Wei-Ming (Sci Rep, 2017)
Hemographic indices have been associated with clinical outcomes in patients with chronic heart failure. We therefore investigated the prognostic values of hemographic indices in patients hospitalized for acute heart failure (AHF). Patients hospitalized primarily for AHF were drawn from an intramural registry. Hemographic indices, including white blood cell counts, neutrophil counts, neutrophil-to-lymphocyte ratio, reciprocal of lymphocyte (RL) and platelet-to-lymphocyte ratio were recorded. Among a total of 1923 participants (mean age 76 ± 12 years, 68% men), 875 patients died during a mean follow-up of 28.6 ± 20.7 months. Except for white blood cell counts, all the other hemographic indices were related to mortality, independently. In a forward stepwise Cox regression analysis among hemographic indices, RL was the strongest predictor (HR and 95% CI per-1SD:1.166,1.097–1.240) for mortality, after accounting for confounders. However, conditioned on the survivals, the hemographic indices were independently related to mortality within 3 years of follow-up, rather than beyond. Hemographic indices were independent risk factors of mortality in patients hospitalized for AHF, especially in patients with impaired left ventricular systolic function. As an acute presentation of inflammation, hemographic indices might be useful to identify subjects at risk of mortality soon after the index hospitalization.